HS-SPME and GC/MS volatile component analysis of Yinghong No. 9 dark tea during the pile fermentation process. (30th September 2021) - Zhang, Wenji; Cao, Junxi; Li, Zhigang; Li, Qiuhua; Lai, Xingfei; Sun, Lingli; Chen, Ruohong; Wen, Shuai; Sun, Shili; Lai, Zhaoxiang
Highlights: Analysis of volatiles changes during pile fermentation of dark tea. Basic volatiles analysis of Yinghong No. 9 dark tea at an industrial scale. On day 20 of pile fermentation, fresh, clean and chest-nutty smell disappeared. On day 40 of pile fermentation, stale, fungus and aged fragrance began to present. β-Myrcene, acetophenone, and terpinen-4-ol may be the key aged aroma compounds. Abstract: Each type of tea has a unique volatile profile due to its variety, processing technologies and origin. Using HS-SPME and GC/MS, we analyzed the changes of volatile components in cultivar Yinghong No. 9 during pile-fermentation every 10 days. A total of 94 compounds showed significant differences during a total of 60 days mainly including alkanes, ketones, esters, terpenes, aromatics and heterocyclic compounds. Interestingly, 13 metabolites were progressively reduced during the first 20 days and remained unchanged in subsequent procedures, while 17 metabolites remained unchanged in the early stage and progressively increased during the last 20 days of pile fermentation, indicating that they are characteristic volatile compounds of raw material sun-dried green tea and dark tea, respectively. β-ionone, phenylethyl alcohol, and a-ionone could be the top three contributed aroma compounds in the final dark tea. Our study provides a theoretical basis for process and quality improvement of Yinghong No. 9.